Exogenous contrast agents for thermoacoustic imaging: An investigation into the underlying sources of contrast. Issue 1 (22nd December 2014) - Ogunlade, Olumide; Beard, Paul
Abstract : Purpose: Thermoacoustic imaging at microwave excitation frequencies is limited by the low differential contrast exhibited by high water content tissues. To overcome this, exogenous thermoacoustic contrast agents based on gadolinium compounds, iron oxide, and single wall carbon nanotubes have previously been suggested and investigated. However, these previous studies did not fully characterize the electric, magnetic, and thermodynamic properties of these agents thus precluding identification of the underlying sources of contrast. To address this, measurements of the complex permittivity, complex permeability, DC conductivity, and Grüneisen parameter have been made. These measurements allowed the origins of the contrast provided by each substance to be identified. Methods: The electric and magnetic properties of the contrast agents were characterized at 3 GHz using two rectangular waveguide cavities. The DC conductivity was measured separately using a conductivity meter. Thermoacoustic signals were then acquired and compared to those generated in water. Finally, 3D electromagnetic simulations were used to decouple the different contributions to the absorbed power density. Results: It was found that the gadolinium compounds provided appreciable electric contrast but not originating from the gadolinium itself. The contrast was either due to dissociation of the gadolinium salt which increased ionic conductivity or its nondissociated polar fraction which increased dielectric polarization loss or a combination of both. In addition, very high concentrations were required to achieve appreciable contrast, to the extent that the Grüneisen parameter increased significantly and became a source of contrast. Iron oxide particles were found to produce low but measurable dielectric contrast due to dielectric polarization loss, but this is attributed to the coating of the particles not the iron oxide. Single wall carbon nanotubes did not provide measurable contrast of any type. Conclusions: It is concluded that gadolinium based contrast agents, iron oxide particles, and single walled carbon nanotubes have little intrinsic merit as thermoacoustic contrast agents. Simple electrolytes such as saline which yield high contrast based on ionic conductivity provide much higher dielectric contrast per unit solute concentration and are likely to be significantly more effective as contrast agents.